The Old Testament library : I & II Samuel : a commentary - Auld, A. Graeme (Louisville, Ky. : Westminster John Knox Press, 2011)
The author demonstrates how all the other personalities in First and Second Samuel--including Samuel, for whom the books were named--are present so that we may see and know David better. These fascinating stories detail the lives of David, his predecessors, and their families. Auld explains that though we read these books from beginning to end, we need to understand that they were composed from end to beginning. By reconstructing what must have gone before, the story of David sets up and explains the succeeding story of monarchy in Israel. --from publisher description
1 Samuel 1-8: a fresh introduction -- 1 Samuel 9-16: two kings anointed by Samuel -- 1 Samuel 17-24: Saul rejected, David in waiting -- 1 Samuel 25-2 Samuel 3: end of Saul, response of David -- 2 Samuel 4-9: David secures his throne -- 2 Samuel 10:1-13:33: disloyalty and disaster -- 2 Samuel 13:34-20:19: David and Absalom -- 2 Samuel 20:20-24:25: concluding perspectives
Includes bibliographical references and indexes
Keywords: Bible. -- Commentaries